Edukasi Kesehatan tentang Hipertensi, Kolesterol, dan Gula Darah pada Masyarakat di Persekutuan Doa Dukuh Kupang Tengah XVI, Surabaya - Sukmawati, Ermalynda; Abigael Grace Prasetiani; Pae, Kristina (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
Health education plays a vital role in raising public awareness about non-communicable diseases such as hypertension, high cholesterol, and diabetes mellitus, which are interrelated and pose risks of severe complications like heart disease and stroke. This community service activity, conducted on November 28, 2024, at the Dukuh Kupang Tengah XVI Prayer Fellowship in Surabaya, aimed to enhance knowledge and prevention of non-communicable diseases. The methods included group health education sessions and health screenings, comprising blood pressure measurement, blood sugar testing, and cholesterol assessment. A total of 22 out of 35 invitees participated, and the results showed that 12 individuals had blood pressure >140/90 mmHg, 11 had cholesterol levels >200 mg/dL, and 6 had elevated random blood sugar levels. The activities involved attendance registration, pre-test questionnaires, health education sessions, post-test questionnaires, health screenings, and distribution of educational leaflets. The findings highlight the importance of maintaining a healthy diet and regular physical activity to prevent the impact of non-communicable diseases. This activity is expected to increase public awareness of the importance of health management and the prevention of further complications.